1982
DOI: 10.1148/radiology.144.1.7089266
|View full text |Cite
|
Sign up to set email alerts
|

Systemic-to-pulmonary collaterals in pathological states: a review.

Abstract: Abnormal systemic-to-pulmonary-artery anastomoses can exist in many pathological conditions and result in a left-to-right shunt. Three such conditions are (a) congenital abnormalities, e.g., pulmonary vein atresia, (b) acquired states, e.g., chronic bronchiectasis, and (c) post-surgical states, e.g., a Mustard procedure for complete transposition. Regardless of the etiology, the anastomosis and resulting shunt produce increased oxygen saturation in the ipsilateral pulmonary artery. Four cases are presented, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…Histologic examination of resected specimens in this series as in other studies (Cudkowics, 1952;Darke and Lewats, 1968;Tadavarthy et al, 1982) showed extensive anastornotic channels between bronchial and pulmonary arteries. Consequently, blood will flow from the high pressure (bronchial) to the low pressure circulation (pulmonary) through the newly established bronchopulmonary shunts.This haemodynamic event was demonstrated in our patients during thoracic arotogrpahy as retrograde filling of the pulmonary artery (Fig.…”
Section: The Haemodynamic Factorsupporting
confidence: 78%
“…Histologic examination of resected specimens in this series as in other studies (Cudkowics, 1952;Darke and Lewats, 1968;Tadavarthy et al, 1982) showed extensive anastornotic channels between bronchial and pulmonary arteries. Consequently, blood will flow from the high pressure (bronchial) to the low pressure circulation (pulmonary) through the newly established bronchopulmonary shunts.This haemodynamic event was demonstrated in our patients during thoracic arotogrpahy as retrograde filling of the pulmonary artery (Fig.…”
Section: The Haemodynamic Factorsupporting
confidence: 78%
“…Thin-walled pulmonary arteries deliver non-oxygenated blood via low-pressure circulation into the lungs for gas exchange and oxygenated blood returns to the heart through pulmonary veins. At the same time, bronchial arteries provide nutrition and oxygen support for the lungs and bronchi via systemic pressure 10 . Classically, bronchial arteries arise from the descending aorta at the level of 5th and 6th thoracic vertebras.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, normal physiological connection occurs between systemic and pulmonary vascular systems; this is the right-to-left shunt, which has no clinical importance. Under normal conditions, this arteriolar plexus is functionally closed without blood flow; these channels may be opened in case of decreased blood flow like pulmonary embolism or may develop neovascularization 10,11 . Despite the hypothesis that these vascular abnormal connections might occur as a response to an intrauterine ischemic event, the lungs and proximal pulmonary arteries were anatomically normal in the present case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…About half of the cases are considered to be congenital in origin and they occur in the presence of cardiac disease or pulmonary artery hypoplasia. 3 An acquired communication develops in patients with cancer or with various infectious or infl ammatory diseases of the lung and the pleura, such as tuberculosis, mycosis, pneumonia, lung abscess, bronchiectasis, and cystic fi brosis. 4 Another contributing factor is chest trauma which can be open, blunt, or iatrogenic after an operation.…”
Section: Discussionmentioning
confidence: 99%